Policy Formulation of Integrated Defense Area Concept to Face Threats as Knowledge - Murfi, Yudhi; Anwar, Syaiful; Swastanto, Yoedhi; Santoso, Totok Imam; Taufik, Robby Mochamad; Maulana, Arman (Journal of Ecohumanism, 2024)
This study discusses the formulation of the concept of an integrated defense area to deal with threats through the establishment of regional offices of the Ministry of Defense in the regions. The research methods used include a descriptive approach, qualitative analysis, and a normative approach to identify problems, analyze obstacles, and formulate policy recommendations. The results of the study indicate that the existence of regional offices of the Ministry of Defense in the regions is not optimal and there are still many obstacles faced, such as coordination between the central and regional governments that needs to be strengthened. The conclusion of this study underlines the need to improve coordination and capacity of regional offices of the Ministry of Defense in the regions to support a more effective national defense policy.